2011
DOI: 10.1099/mic.0.043596-0
|View full text |Cite
|
Sign up to set email alerts
|

Presence of Salmonella pathogenicity island 2 genes in seafood-associated Salmonella serovars and the role of the sseC gene in survival of Salmonella enterica serovar Weltevreden in epithelial cells

Abstract: The type III secretion system encoded by the Salmonella pathogenicity island 2 (SPI-2) has a central role in the pathogenesis of systemic infections by Salmonella. Sixteen genes (ssaU, ssaB, ssaR, ssaQ, ssaO, ssaS, ssaP, ssaT, sscB, sseF, sseG, sseE, sseD, sseC, ssaD and sscA) of SPI-2 were targeted for PCR amplification in 57 seafood-associated serovars of Salmonella. The sseC gene of SPI-2 was found to be absent in two isolates of Salmonella enterica serovar Weltevreden, SW13 and SW39. Absence of sseC was co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 44 publications
1
22
2
Order By: Relevance
“…16 Although all serovars of Salmonella enterica are considered pathogenic to man, 17 the distribution of virulence genes in serovars is not well understood. 18 An encompassing scientific literature review also confirms the negligible presence of research focussing on understanding virulence determinants associated with the isolated Salmonella serovars with special reference to DOD. An accelerated dissemination of resistant pathogenic organisms from one geographic location to another has occurred as a result of globalization and international trade over the past decade.…”
Section: Introductionmentioning
confidence: 72%
“…16 Although all serovars of Salmonella enterica are considered pathogenic to man, 17 the distribution of virulence genes in serovars is not well understood. 18 An encompassing scientific literature review also confirms the negligible presence of research focussing on understanding virulence determinants associated with the isolated Salmonella serovars with special reference to DOD. An accelerated dissemination of resistant pathogenic organisms from one geographic location to another has occurred as a result of globalization and international trade over the past decade.…”
Section: Introductionmentioning
confidence: 72%
“…Despite an obvious sequence similarity of type III secretion proteins present in different GIs, DNA compositional analysis showed that these virulence factors evolved independently several times by gene recombination. Type III secretion system in the SPI-2 PAI of Salmonella (cell B5) is well characterized [68], [71]. This is a relatively old gene insert in contrast to the type III secretion proteins of the PAI LEE in Escherichia which are of recent horizontal gene exchange activity (C5–D5 in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…For instance, the rate of ciprofloxacin resistance in clinical E. coli isolates has increased from 4.3% to 16.7% between 1998 and 2013 in southeast Austria. Such resistance is attributed to the misuse of antibiotics and will ultimately increase the cost of treatment, prolong the illness, and increase the rate of mortality (Van et al 2007;Bhowmick et al 2011;Fortini et al 2011;Pavlickova et al 2015). Unfortunately, more than half a million people worldwide die each year from antibiotic-resistant bacterial infections (Davies et al 2013).…”
Section: Antibiotic-associated Intestinal Dysbiosismentioning
confidence: 99%